If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + -7g + 14p = 0 Reorder the terms: -7g + 3p + 14p = 0 Combine like terms: 3p + 14p = 17p -7g + 17p = 0 Solving -7g + 17p = 0 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-17p' to each side of the equation. -7g + 17p + -17p = 0 + -17p Combine like terms: 17p + -17p = 0 -7g + 0 = 0 + -17p -7g = 0 + -17p Remove the zero: -7g = -17p Divide each side by '-7'. g = 2.428571429p Simplifying g = 2.428571429p
| .18(6)+0.03x=.09(24+x) | | X+1.5(x+2)=58 | | 5+3x-7= | | 10n+15n= | | 4[2x-(3-x)+5]=6x-28 | | x/5=4x+1 | | 50x+5897-4312=386135 | | 243=9(10+x) | | 2+u=0 | | 3(3x-2)-5x=x-3 | | 0.10+0.05(52-x)=450 | | (X+2)7=40 | | 6y+1=3x+1 | | 28w-12=16w-30 | | 3r^2-2r-3=0 | | 6x-16=4x+30 | | x^2-5xy+6y^2=0 | | (7x-2)(-5x+6)= | | a^2+14a-99=0 | | -2m-5m=9m-12 | | 7n+1=2n-4 | | -x+19+3x+19=4 | | 50+2x=120-5x | | 24+8=24+2x | | 7y-4=-14 | | u(u^4-13u^2+36)=0 | | 11+m=m-.25 | | x+1=12+3x | | u(u^4-13u^2+63)=0 | | 8a-5a=3a | | 24+2x=24+8 | | 13.4=8.5-x |